Produtividade do feijoeiro sob supressão de irrigação em diferentes fases fenológicas - Miorini, Thomas José Justo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
O feijão (Phaseolus vulgaris L.) tem grande expressão no cenário econômico e social do Brasil, pois além de ser um alimento básico da população brasileira, faz parte da renda do pequeno e médio produtor rural. A hipótese deste trabalho é que a supressão do fornecimento de água em alguma fase ou em algumas fases do desenvolvimento do feijoeiro irrigado sempre resulta em redução de produtividade de, pelo menos, 20%. O objetivo foi de analisar a influência do uso da irrigação em diferentes estádios fenológicos do feijoeiro sobre o desempenho dos componentes de produção do feijão do grupo Carioca, cultivar IAC Alvorada. O presente trabalho foi desenvolvido na Fazenda Experimental Lageado / Departamento de Engenharia Rural, da Faculdade de Ciências Agronômicas, UNESP, campus de Botucatu. O delineamento estatístico utilizado foi o de blocos ao acaso, com 16 tratamentos e oito repetições, sendo cada parcela de 2,0 m x 4,5 m (Experimento I – campo) e 32 tratamentos e 4 repetições em vasos de 9 litros (Experimento II – casa de vegetação). Os tratamentos foram baseados em diferentes épocas de aplicação de lâminas de água em períodos críticos na cultura do feijão. No Experimento I – campo, as fases críticas consideradas foram: fase vegetativa, floração, enchimento de grãos e maturação...

Bean (Phaseolus vulgaris L.) is widespread in the social and economic scene in Brazil, as well as being a staple of Brazilian population, helps small and medium-income farmers. The hypothesis is that if the water supply is suppressed in just one of the five development stages or in some phases of development of irrigated beans, it can result in reduction productivity of, at least, 20%, allowing water economy. The objective of this study was to compare the performance of bean Carioca group IAC Alvorada yield components, with irrigation suppression in each of the phenological phases and no irrigation and irrigated in all stages. The study was conducted at Agronomical Sciences College, UNESP, Botucatu, SP, Brazil. The statistical design was the randomized block with sixteen treatments and eight replications, each plot was 2.0m X 4.5m (Experiment I – Field) and thirty-two treatments and four replications in vase of 9l (Experiment II – Greenhouse). Treatments were based on different application times water depth at critical periods in the bean crop. In Experiment I – Field, the critical phases were: vegetative stage, flowering, grain filling and maturation. In Experiment II – Greenhouse, the critical phases were: VI (V1 – V3), VII (V4 – flowering), flowering, pod formation and filling grain. Irrigations were performed to increase the water soil content to the field capacity using a class A Pan (Experiment I) and using tensiometers (Experiment II). Variables evaluated were: average number of pods per plant, pods of average size, average number of grains per pods, weight of 100 grains and productivity. Data were analyzed using SAS statistical program, subjected to analysis of variance and “t” test at 5% probability, as well as study of orthogonal contrasts. In Experiment I – Field, the yield components were higher affected when it occurred irrigation’s... (Complete abstract click electroni
Keywords: Feijão - Irrigação; Bean - Irrigation